Architectural Physical and Spatial Characteristics of Chinatown Shop Houses in Singaraja City, Bali - Putu Nanda Indirahajeng; Dyah Titisari Widyastuti (Architectural Research Journal, 2023)
Since North Bali is in a very advantageous location and can support navigation technology systems that are still basic, trade relations can be established through ships that frequently travel through the northern Bali region. Beginning in the northern region and a region that was influenced by the Port of Buleleng, Chinatown shophouses began to grow throughout time. The study uses a qualitative descriptive methodology to explain the conclusions drawn from both primary and secondary sources of information. The architectural features of Chinatown shophouses are discussed in this study, including their physical characteristics, figural qualities connected to their shapes and materials, and spatial characteristics relating to their functions and zoning of space. Physical characteristics are categorized into types of buildings according to the number of floors and the materials used, and the typology is based on the era in which the shophouse was constructed. The results of this study on spatial character reveal that a building’s ground floor is divided into front, middle, and back, with the front zone serving a commercial function, the middle zone serving a residential function, and the back zone serving a service function. On both the ground floor and the top floor, the altar room is always located in the front zone.